The impact of parent, peers and social media on shaping the financial behavior of Generation Z - Nie, Chen (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to investigating the influence of media, social environment, and parental advice on the financial behavior of Generation Z in Indonesia. The research focuses on understanding how these factors shape the financial attitudes and behaviors of Generation Z, who face unique challenges in their financial journey. This research study utilizes a quantitative research methodology. The findings reveal that media has a positive influence on the financial behavior of Generation Z, highlighting the impact of media consumption on financial decision-making. Additionally, parental advice and guidance were found to play a vital role in providing financial literacy instruction to Generation Z. The study emphasizes the importance of collaborative efforts among schools, parents, financial institutions, and policymakers to enhance financial literacy and promote responsible financial behavior among young individuals. The findings contribute to the existing literature by providing valuable insights into the specific influences on Generation Z's financial behavior, including financial attitude, peer influence, parent influence, and social media exposure. These insights can inform the development of targeted interventions and educational initiatives to equip Generation Z with the necessary skills to navigate their financial futures successfully and promote positive financial outcomes.